Mengenali Bentuk dan Bahaya Perundungan di Sekolah Dasar - Trischintyadevi, Luh Komang Ayu; Sudarsana, I Ketut (Jayapangus Press, 2025)
Bullying is a negative act committed by individuals or groups with the intent to harm victims physically or mentally. Although often associated with adolescents or adults, bullying also occurs at the elementary school level. Children at a young age can become both perpetrators and victims of bullying, either consciously or unconsciously. If left unaddressed, bullying can lead to serious consequences such as long-term psychological trauma and even death. This study aims to explore the dangers of bullying and examine the role of teachers in preventing bullying in elementary school environments. This research employed a literature review method, analyzing various scholarly sources, journals, and relevant case reports. The findings reveal that bullying in elementary schools frequently manifests in the form of teasing, social exclusion, physical intimidation, and verbal abuse. These actions negatively impact students’ self-esteem, academic performance, and mental well-being. Teachers play a crucial role in preventing and addressing bullying. Preventive actions taken by teachers include conducting regular socialization and educational programs for students about the dangers of bullying, fostering open communication among teachers, students, and parents, and following up on reported bullying cases in a firm and thoughtful manner. The study concludes that bullying in elementary schools is a serious issue requiring the attention of all stakeholders. Teachers, as front-line educators, hold a strategic responsibility in creating a safe, supportive, and violence-free learning environment.